EYL Teachers Communication Strategies in Synchronous and Asynchronous Online Teaching and Learning - Wiwik Mardiana; Taswirul Afkar (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
This current research aims at exploring the teachers communication strategies in online learning context, i.e. synchronous and asynchronous, explaining the challenges and solutions, and finding out the factors influencing. This qualitative research employed observation and interview to collect the data. The participants were two teachers of five grade at one of Bilingual schools in Mojokerto. Source and technique triangulation were carried out to get the validity of the data. In analyzing the data, the researchers displayed the percentage to know the dominant data, then explore the characteristics and interpret the intentions, challenges, solutions, and factors. The findings revealed that translation, praising, code-switching, comprehension check, and other repetition were the most dominant strategy used in synchronous mode. The teachers did not fulfill all components of strategies in explaining the materials in asynchronous mode. The challenges coped by the teachers were not merely due to online classroom; nevertheless, the teachers initiated the solutions. There were four interrelated factors influencing the use of communication strategies. The strategies employed in both synchronous and asynchronous modes were generally to facilitates students in online context. This research suggests that teachers communication strategies are beneficial to encourge students in learning English especially in online context. Some aspects found in this research are further discussed.